The interaction of core-collapse supernova ejecta with a companion star - Liu, Zhengwei; Tauris, T. M.; Röpke, Friedrich; Moriya, T. J.; Kruckow, M.; Stancliffe, R. J.; Izzard, R. G. (Astronomy and astrophysics, 2015)
The progenitors of many core-collapse supernovae (CCSNe) are expected to be in binary systems. After the SN explosion in a binary, the companion star may suffer from mass stripping and be shock heated as a result of the impact of the SN ejecta. If the binary system is disrupted by the SN explosion, the companion star is ejected as a runaway star, and in some cases as a hypervelocity star. By performing a series of three-dimensional (3D) hydrodynamical simulations of the collision of SN ejecta with the companion star, we investigate how CCSN explosions affect their binary companion.
Gesehen am 29.06.2020